Програмна реалізація безпеки застосувань для обміну інформацією - Міхневич, І. Д. (ХНУРЕ, 2019)
In this work, the main object of research is the development of application software for the transmission and encryption of text messages. The methods of making language based on object-oriented direction C # development environment and Microsoft Visual Studio, using object-oriented programming approach. The result of the work done is functioning application that can send and receiving messages.